In-Vitro Carbofuran Induced Genotoxicity in Human Lymphocytes and Its Mitigation by Vitamins C and E. Issue 3 (26th May 2013) - Sharma, Ratnesh Kumar; Sharma, Bechan
Abstract : Various efforts have been made in past in order to predict the underlying mechanism of pesticide-induced toxicity using in vitro and animal models, however, these predictions may or may not be directly correlated with humans. The present study was designed to investigate the carbofuran induced genotoxicity and its amelioration by vitamins C and E by treating human peripheral blood lymphocytes (PBLs) with different concentrations (0, 0.5, 1.25, 2.5, 3.75 and 5.0  μ M) of this compound. The treatment of PBLs with carbofuran displayed significant DNA damage in concentration dependent manner. The carbofuran induced genotoxicity could be ameliorated to considerable extent by pretreatment of PBLs with equimolar (10  μ M) concentration of each of the vitamins C and E; the magnitude of protection by vitamin E being higher than by vitamin C. Also, it was found that the level of protection by these vitamins was higher when PBLs were treated with lower concentrations of pesticide. The significant DNA damage as observed by H2 O2, a positive control in the present study, and its amelioration by natural antioxidants (vitamins C and E) lend an evidence to suggest that carbofuran would have caused genotoxicity via pesticide induced oxidative stress.